2012
DOI: 10.1007/s10853-012-6597-6
|View full text |Cite
|
Sign up to set email alerts
|

A study on environmental stress cracking in nano-SiO2-filled polycarbonate

Abstract: In this study, the environmental stress cracking (ESC) resistance of nano-SiO 2 particle-filled polycarbonate (PC) was investigated at room temperature by using a fracture mechanical test method. Two PC-based nanocomposites with nano-SiO 2 content of 1 and 4 vol% were compounded using a twin-screw extruder. The incorporation of nanoparticles into PC leads to an improvement in ESC resistance, which increases with increased filler loading up to 4 vol%. Fractography analyses suggest that the formation of cavities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…In isopropanol, the deformation area develops in two directions, displaying a similar “candle flame” pattern. The appearance of this shape can be explained by the crack‐layer theory . A smaller crazing area with three major directions of deformation spreading surround the crack‐tip is observed in methanol, indicating a different fracture mechanism in this environment .…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…In isopropanol, the deformation area develops in two directions, displaying a similar “candle flame” pattern. The appearance of this shape can be explained by the crack‐layer theory . A smaller crazing area with three major directions of deformation spreading surround the crack‐tip is observed in methanol, indicating a different fracture mechanism in this environment .…”
Section: Resultsmentioning
confidence: 88%
“…reported that the incorporation of organically modified montmorillonite into rubber‐toughened polyester produced a product with improved ESC resistance in sodium hydroxide and hydrochloride acid solutions. Our previous research also established that the incorporation of nanofillers improves the ESC resistance in isopropanol and significantly increases the service lifetime of PC nanocomponents …”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations